De l’art pour changer la rue ? Étude du rôle de la norme de gentrification dans la construction de projets de street art à Bruxelles et Marseille - Anton Olive-Alvarez (Métropoles)
In recent years, city projects using street art murals have flourished all over Europe. For many scholars, these projects can be considered as an appropriation of a subversive subculture for gentrification purposes. The present article aims to discuss the perspective of street art policy as a means of gentrification by looking at the constitution of street art projects, rather than at their effects. In order to do so, two projects are investigated in central neighbourhoods in Brussels and Marseille respectively. The paper shows that street art policies are driven by very heterogeneous coalitions of actors (artists, storekeepers, city representatives…). These actors manage to unite despite their differences because they share a common language that presents street art as a tool to increase the attractiveness of working-class neighbourhoods for new categories of inhabitants. However, these various actors do not necessarily fully subscribe to that gentrification norm. Rather, they refer to it because it offers them retributions in the specific fields in which they are engaged. The analysis of the formation of each of these coalitions by replacing every actor in the logic of his own field helps to understand the variety of results that can emerge from projects that are similar in type.